Dual allosteric modulation of opioid antinociceptive potency by α2A-adrenoceptors. (December 2015) - Chabot-Doré, Anne-Julie; Millecamps, Magali; Naso, Lina; Devost, Dominic; Trieu, Phan; Piltonen, Marjo; Diatchenko, Luda; Fairbanks, Carolyn A.; Wilcox, George L.; Hébert, Terence E.; Stone, Laura S.
Abstract: Opioid and α2 -adrenoceptor (AR) agonists are analgesic when administered in the spinal cord and show a clinically beneficial synergistic interaction when co-administered. However, α2 -AR antagonists can also inhibit opioid antinociception, suggesting a complex interaction between the two systems. The α2A -AR subtype is necessary for spinal adrenergic analgesia and synergy with opioids for most agonist combinations. Therefore, we investigated whether spinal opioid antinociception and opioid-adrenergic synergy were under allosteric control of the α2A -AR. Drugs were administered intrathecally in wild type (WT) and α2A -knock-out (KO) mice and antinociception was measured using the hot water tail immersion or substance P behavioral assays. The α2A -AR agonist clonidine was less effective in α2A -KO mice in both assays. The absence of the α2A -AR resulted in 10–70-fold increases in the antinociceptive potency of the opioid agonists morphine and DeltII. In contrast, neither morphine nor DeltII synergized with clonidine in α2A -KO mice, indicating that the α2A AR has both positive and negative modulatory effects on opioid antinociception. Depletion of descending adrenergic terminals with 6-OHDA resulted in a significant decrease in morphine efficacy in WT but not in α2A -KO mice, suggesting that endogenous norepinephrine acts through the α2A -AR to facilitate morphine antinociception. Based on these findings, we propose a model whereby ligand-occupied versus ligand-free α2A -AR produce distinct patterns of modulation of opioid receptor activation. In this model, agonist-occupied α2A -ARs potentiate opioid analgesia, while non-occupied α2A -ARs inhibit opioid analgesia. Exploiting such interactions between the two receptors could lead to the development of better pharmacological treatments for pain management. Graphical abstract: Highlights: The role of α2A -adrenoceptors (ARs) in spinal opioid antinociception was investigated. The α2A -AR is necessary for analgesic synergy between clonidine and opioid agonists. Opioid antinociception is enhanced in α2A -AR-KO mice. A model of activation state-dependent allosteric modulation is proposed. The model has implications for allosteric modulation of other G protein-coupled receptor pairs.